The effect of spiritual care education on hope in the elderly residents of nursing homes in Hamadan province in 2018 - Seyed Reza Borzou; Danial Shadi; Narges Kalvandi; Ali Afshari; Leili Tapak (Tehran University of Medical Sciences, 2020)
Background & Aim: Frustration is one of the important psychological consequences for the elderly in the nursing home. Spiritual care is a unique aspect of nursing care that can be a strong response to the dealing with frustration. The aim of this study was to determine the effect of spiritual care education on hope in the elderly residents of nursing homes. Methods & Materials: The present study was a before-and-after semi-experimental study, conducted in 2018 on 35 elderly residents of nursing homes in Hamadan, assigned into two groups of intervention (35 people) and control (35 people). At the beginning of the study, both groups completed the Schneider hope scale. For the intervention group, the intervention based on spiritual care was performed in three sessions. The post-test was performed for both groups after one month. Spearman correlation and Kruskal-Wallis tests were used to analyze the data through the SPSS software version 16. Results: There was no significant difference in overall hope score between the groups of intervention (22.94±9.80) and control (25.94±3.86) before the intervention (P=0.085); but after the intervention, there was a significant difference between the intervention (42.94±6.04) and control (23.80±4.09) groups (P<0.001). Conclusion: Considering the positive effect of spiritual care on hope in the elderly in this research, planning for spiritual education is essential in this group of people.